Development of acute pancreatitis after Nissen fundoplication. Issue 2 (April 2015) - Inoue, Mikihiro; Uchida, Keiichi; Otake, Kohei; Okigami, Masato; Maji, Tomoaki; Kusunoki, Masato
Abstract Acute pancreatitis subsequent to Nissen fundoplication for gastroesophageal reflux disease (GERD) is an extremely rare adverse event. We describe a pediatric case of acute pancreatitis resulting from superior mesenteric artery syndrome (SMAS) and gas bloat after fundoplication. Gas bloat is one of the known postoperative complications after Nissen fundoplication. Poor nutrition status, which is often associated with severe pediatric GERD, is a risk factor for SMAS. In this case, development of gas bloat and SMAS led to the formation of a closed loop and increased intraluminal pressure of the duodenum and pancreatic duct. Many pediatric patients who need anti‐reflux surgery face the risk of developing this entity. Preventive measures, such as treatment with prokinetics and frequent small‐volume meals, should be considered until improvement of nutritional status after fundoplication.